Une forme spontanée de figuier (Ficus carica L.), le nābūt - Younes Hmimsa; Yildiz Aumeeruddy-Thomas; Mohammed Ater (Revue d'ethnoécologie)
The fig tree is an emblematic fruit tree of the Mediterranean region as much as olive, grapevine or almond. Its cultivation is widespread in the Rif Mountains where it has a characteristic feature of traditional agroecosystems. Varietal diversity is exceptionally high, estimated at over 100 local varieties. From a socio-economic perspective, the fig tree is highly appreciated by the local populations. Indeed, beyond its food and economic importance, the fig tree has an important heritage value. The ethnobiological approach has provided explanatory elements to the various issues related to the social processes leading to the selection and conservation of this varietal diversity.Within this diversity, the coexistence of cultivated (named varieties) and spontaneous (nābūt) forms in traditional orchards is noted. This leads us to explore the origin and conservation of the diversity of the fig tree in relation to the presence of spontaneous forms. Indeed, nābūt, typical variety of the spontaneous fig tree which propagates sexually though seedlings as opposed to cultivated varieties – which are propagated clonally by men through cuttings - is controversial depending on the zones, the uses and the practices. These aspects will be the subject of our communication.